Rancang Bangun Alat Kalibrasi Side Slip Tester Pada Alat Pengujian Kendaraan Bermotor Muller BEM10000 - Budi Sulistyo, Aris; Arta, I Wayan Yogi (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2025)
Calibration of testing equipment is an integral part of public service, based on the Regulation of the Director General of Land Transportation No. SK2405/AJ.402/DRDJ/2014 concerning Standard Operational Procedures for the Implementation of Motor Vehicle Equipment Calibration. The motorized vehicle testing equipment that must be calibrated includes CO/HC emission testers, smoke thickness testers, headlight testers, brake testers, weight testers, sound level testers, front wheel toe-in/side slip testers, glass darkness testers, and speedometer testers. The side slip tester plays a crucial role in assessing vehicle durability and comfort. Currently, the calibration of side slip testers is performed using manual methods. This approach can lead to suboptimal calibration accuracy and a longer execution time. Consequently, this research focuses on the design and construction of a new calibration tool specifically for the side slip tester. The development of a microcontroller-based side slip tester calibration tool provides a significant improvement over the manual method. This new tool offers several advantages, including easier operation, a reduced need for personnel, and enhanced time efficiency. The implementation of this calibration tool is expected to lead to a significant performance improvement in the calibration process of side slip testers.